Intrawound Vancomycin Powder Decreases Staphylococcal Surgical Site Infections After Posterior Instrumented Spinal Arthrodesis. Issue 10 (December 2015) - Heller, Aaron; McIff, Terence E.; Lai, Sue-Min; Burton, Douglas C.
Abstract : Study Design: A retrospective historical cohort design. Objective: To determine what effect the addition of intrawound vancomycin powder to the prophylactic regimen of posterior instrumented spinal arthrodesis procedures has had on acute surgical site infections (SSIs). Summary of Background Data: SSIs are known complications in instrumented spinal arthrodesis procedures, and are predominately caused by Staphylococcus aureus . Recent reports have suggested that placing vancomycin powder into the surgical wound before closure prevents SSIs in spinal surgery. Risk factors for SSIs in the setting of intrawound vancomycin powder use have not been previously reported on. Materials and Methods: SSI rates after 342 posterior instrumented spinal arthrodeses (October 2008–September 2011) in which intrawound vancomycin powder was used in addition to the standard antimicrobial prophylaxis (Vanco cohort) were compared with 341 posterior instrumented spinal arthrodeses (April 2005–October 2008) in which no vancomycin powder was added (non-Vanco cohort). Both 2 sample t test and χ 2 test (Fisher where appropriate) were used for group comparisons. A subanalysis of the Vanco cohort was undertaken to identify risk factors for SSIs despite intrawound vancomycin use. Results: There was a significant reduction in the number of acute staphylococcal SSIs in the Vanco cohort (1.1%) compared with the non-Vanco cohort (3.8%; P =0.029). Deep staphylococcal infections decreased to 0 compared with 7 in the non-Vanco cohort (2.1%; P =0.008). Deep methicillin-resistant S. aureus infections decreased to 0 compared with 5 in the non-Vanco cohort (1.5%; P =0.031). A subanalysis of the Vanco cohort identified that being discharged to an inpatient rehabilitation or skilled nursing facility was associated with developing a SSI. Conclusions: Intrawound vancomycin powder use has decreased the rate of acute staphylococcal SSIs in our posterior instrumented spine arthrodesis surgeries. Patients who are discharged to skilled nursing or rehabilitation facilities are at an increased risk for developing SSIs despite intrawound vancomycin use.